Alcoholic hydroxyl functionalized partially reduced graphene oxides for symmetric supercapacitors with long-term cycle stability. (1st August 2019) - Zhang, Yong; Wen, Guangwu; Fan, Shan; Ma, Wenhui; Li, Shuhua; Wu, Tao; Yu, Zhaochuan; Zhao, Baoru
Abstract: In this paper, thin-walled 3D alcoholic hydroxyl functionalized partially reduced graphene oxides (APRGs) with high alcoholic hydroxyl content are easily prepared using graphene oxide (GO) dispersions via an eco-friendly one-step hydrothermal method. A small amount of Tris(hydroxymethyl)methyl aminomethane (THAM) is used as the alcoholic hydroxyl source, 3D structural modifier, nitrogen doping and reducing agents, at the same time. The externally introduced alcoholic hydroxyl groups cannot only improve the wettability of the APRGs samples, but also increase their specific capacitances. Most importantly, because the chemical nature of the alcoholic hydroxyl group is stable, it imparts the APRGs sample excellent cycle stability. The APRG-30 sample with high alcoholic hydroxyl content (9.34 at%) in the wet state exhibits a high specific capacitances of 260.2 F g -1 at 0.3 A g -1 in 6 M KOH aqueous electrolyte with an excellent rate capability of 89.8% at 10 A g -1 . In particular, a specific capacitance increasing of 4.7% after 10, 000 cycles at 10 A g -1 is obtained, demonstrating its outstanding long-term cycle stability. These results imply that the APRG-30 sample is suitable for use as supercapacitor electrode materials. Highlights: APRGs samples are successfully prepared by a one-pot hydrothermal method. APRGs samples have a thin-walled 3D porous structure. APRGs samples have high content of alcoholic hydroxyl group. The APRG-30 based electrode exhibits a high specific capacitance of 260.2 F g -1 . The APRG-30 based symmetric supercapacitors present outstanding long-term cycle stability.